A Novel Cloud-Based Temperature Monitoring Service to Datacenter Environment - Khaleel, Mustafa Ibrahim; Boskany, Najmadin Wahid; Abdulla, Miran Taha (Kurdistan Journal of Applied Research, 2018)
As temperature-efficient of cloud datacenters becomes one of many challenges faces the engineers in today’s business environment, virtualized monitoring the resources over these datacenters is the cloud provider’s interest in a way the providers can control their temperature remotely anywhere around the world. Techniques proposed by existing works are focused on executing many cloud modules on less cloud-server which cannot be practical because massive volume of cloud modules will be scheduled by cloud tenants. This motivated us to present a novel solution and propose a real-time temperature aware for cloud network datacenters. The proposed paradigm is constructed based on defining dual thresholds per datacenter to control the level of temperature. Moreover, we have set the upper threshold to 25 degree and the lower one to 15 degree. Surpassing these values alerts network administrator through cloud-based software service to operate the cooling unit(s). The microcontrollers that have been incorporated are both Arduino and GSM Shield. The simulation results showed that our heuristic had the ability to control the temperature per datacenter approximately 63%.